2017
DOI: 10.5005/jp-journals-10024-2179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interimplant Distance and Cyclic Loading on the Retention of Overdenture Attachments

Abstract: Aim:The purpose of this in vitro study was to investigate the effect of interimplant distance and cyclic loading on the retention of two locator attachment systems. Materials and methods:A total of 72 acrylic resin blocks were fabricated and divided into six groups of six pairs each. Locators of DIO and 3i implant systems were positioned on analogs in three different interimplant distances (19, 23, and 29 mm). The blocks were attached to a universal testing machine, and 1,440 dislodging cycles by the force of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…In 2012, Shayegh et al conducted a study to compare the effects of various interimplant distances and cyclic dislodgment on the retention of Locator attachments. 26 The results showed that as in our study, cyclic dislodgment resulted in decreased retention of the attachment.…”
supporting
confidence: 74%
“…In 2012, Shayegh et al conducted a study to compare the effects of various interimplant distances and cyclic dislodgment on the retention of Locator attachments. 26 The results showed that as in our study, cyclic dislodgment resulted in decreased retention of the attachment.…”
supporting
confidence: 74%
“…The study of Tabatabaian et al [ 23 ] showed a significantly greater resistance to dislodging forces for ball-retained overdenture at 35 mm inter-implant distance than at 15 and 25 mm inter-implant distances. Moreover, Shayegh et al [ 24 ] found that increasing the inter-implant distance between two un-splinted attachments from 19 to 23 mm and from 23 to 29 mm has significantly increased the initial retention.…”
Section: Discussionmentioning
confidence: 99%
“…The value was measured at the first cycle and then following completion of each 90-cycle simulating one month until completing 1080 placement/removal cycles simulating one year of use, three cycles per day assuming that an overdenture is expected to be removed three times a day for cleaning. The dislodgment rate was kept at one cycle per 3 seconds to allow nylon attachment elastic recovery [ 31 ].…”
Section: Methodsmentioning
confidence: 99%